2017
DOI: 10.1371/journal.pone.0180426
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Merkelcell polyomavirus (MCPyV) large T-antigen in Merkel cell carcinoma lymph node metastases predicts poor outcome

Abstract: BackgroundThe aim of this study was to determine the prevalence of MCPyV in Merkel cell carcinoma (MCC) primaries versus lymph node metastasis and to evaluate possible prognostic factors.MethodsSamples of MCC primaries and lymph node metastases were stained immunohistochemically for the MCPyV large T-antigen and expression was compared to patients´ clinical outcome.Results41 MCC patients were included. 33 (61%) out of 54 specimens were MCPyV-positive in the immunohistochemistry. 15 (47%) out of 32 primary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
7
2
Order By: Relevance
“…This finding would indicate that patients with MCPyV positive tumour specimens suffer a higher rate of metastatic disease. In current literature, it was previously suggested that the MCPyV status correlates with patients’ prognosis . However, in contrast to our findings Sihto et al concluded that patients with MCPyV positive MCCs have a better survival than those with MCPyV negative tumours.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding would indicate that patients with MCPyV positive tumour specimens suffer a higher rate of metastatic disease. In current literature, it was previously suggested that the MCPyV status correlates with patients’ prognosis . However, in contrast to our findings Sihto et al concluded that patients with MCPyV positive MCCs have a better survival than those with MCPyV negative tumours.…”
Section: Discussioncontrasting
confidence: 99%
“…In current literature, it was previously suggested that the MCPyV status correlates with patients' prognosis. [49][50][51] However, in contrast to our findings Sihto et al 50…”
Section: Discussioncontrasting
confidence: 99%
“…Additional biomarkers previously explored in MCC include: nuclear survivin expression [85]; activating mutations in PIK3CA, a key kinase in the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) oncogenic pathway MCC [86]; expression of hedgehog pathway molecules [87,88], although hedgehog inhibitors have not shown efficacy against MCC [89]; and markers of cell cycle and cell proliferation [90,91]. In general, MCPyV + MCCs have been shown to have a better prognosis compared to MCPyV-MCCs [39,86,92,93]-both when primary and metastatic lesions are tested [94], although not all studies agree [95,96].…”
Section: Prognostic Biomarkers In Merkel Cell Carcinomasmentioning
confidence: 99%
“…After WGA of single CTCs, analysis of copy number aberrations and MCPyV status in such cells showed that tumor tissue biopsies were mainly MCPyV + , whereas single CTCs from the same patient showed a more heterogeneous profile for detection of the polyomavirus. Heterogeneity of MCPyV status was already described, notably between primary and metastatic tumors 35 . These discrepancies might be explained by (i) a bias of amplification of the CTC genome, (ii) a loss of viral DNA upon cancer cell detachment and dissemination, or (iii) the presence of MCPyV − clones in metastases, suggested by the hit-and-run theory, as discussed previously 36 .…”
Section: Discussionmentioning
confidence: 84%